Uso de geofísica para determinar el perfil de suelo en las formaciones geológicas de la ciudad de Ocaña, Norte de Santander - Romel Jesús Gallardo-Amaya; Luís Fernando Ortega-Lozano; Gustavo Guerrero-Gómez (Mundo Fesc)
Currently, the use of geophysical techniques to establish the shear wave velocity profile of a soil is widespread. One of these techniques is microtremor refraction, which uses ambient noise to measure the shear wave velocity (Vs), a parameter that allows establishing the soil profile in accordance with the Colombian Regulations for Earthquake-Resistant Construction. For the development of the research, geophysical tests were carried out in seven sectors of the southeastern part of the city: 15 lines in sectors with materials from a sedimentary geological formation and 15 in a sector with materials from an igneous geological formation. The probe lines were constructed with a length of 58 m, in order to establish the variation in shear wave velocity in the upper 30 m of the soil profile. It was found that the shear wave velocities in the soil profile with materials of sedimentary origin are lower than those determined in the soil profile with materials derived from igneous rocks. The average shear wave velocity values ​​determined were 402 m/s for the 30 m soil profile containing sedimentary materials and 688 m/s for the igneous soil profile. These values ​​indicate a type C soil profile according to the Colombian Earthquake Resistant Standard. Additionally, the shear wave velocity profiles determined indicate significant variability in the different sectors of the city where sedimentary materials are present.